Implementasi Business Intelligence Menggunakan Tableau Untuk Visualisasi Data Dampak Bencana Banjir di Indonesia - Dandie Triyanto; Muchammad Sholeh; Firman Noor Hasan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Indonesia is a region prone to natural disasters, one of which is flooding. The purpose of this study was to visualize the impact areas of the natural flood disaster in all provinces of Indonesia by implementing business intelligence, which displays the number of submerged houses, damaged houses, and public facilities, as well as the number of dead, missing, and injured victims. The method of this research was obtained in the form of a dataset sourced from the National Disaster Management Agency from January 1, 2008, to January 31, 2023, using the business intelligence platform Tableau Public. The results of the research are in the form of reports and dashboards that display data visualization for flood-affected provinces in Indonesia. In conclusion, based on the visualization results obtained, the province that experienced the impact of the flood disaster was West Java with the highest number of 1,538,125, and based on all cities and districts in February 2021, there were 221,715 The most damaged houses and public facilities, namely 4,929 houses and 76,795 public facilities; and the most flood victims, namely 173 missing victims in 2010, 500 dead victims in 2010, and 69,656 injured victims in 2008.